IDDF2022-ABS-0161 Tertiary lymphoid structures promote hepatocellular carcinoma immunotherapy. (2nd September 2022) - Li, Jinyang; Yang, Xinxiang; Zhu, Jiye; Man, Kwan
Abstract : Background: Tertiary Lymphoid Structures (TLSs) develop in non-lymphoid tissues at sites of chronic inflammation, including hepatocellular carcinoma (HCC). A favorable impact of TLSs on preventing tumor invasion and metastasis has been observed in various tumors. In addition, the presence of intra-tumoral TLSs is associated with better survival and immunotherapy response. However, the roles of TLSs in HCC are still controversial. Methods: The expression of TLSs in HCC tumors was detected by H&E staining and multiplex immunohistochemistry (mIHC). Expression levels of various immune checkpoints were evaluated by qRT-PCR. After nivolumab treatment, 15 patients were divided into the responsive and non-responsive groups according to the percentage of necrotic tumor areas in tumor sections. Results: The representative mIHC image of TLS in the HCC tumors was shown in IDDF2022-ABS-0161 Figure 1A. 119 patients not receiving immunotherapy were divided into two groups according to the presence of TLSs in tumors. Multivariate analyses showed that the presence of TLSs in tumors was associated with HCC recurrence and worse overall survival (IDDF2022-ABS-0161 Table 1B, IDDF2022-ABS-0161 Table 1C). HCC patients with intra-tumoral TLS + had a higher 5-year recurrence rate and shorter overall survival than patients without TLSs (IDDF2022-ABS-0161 Figure 1D). In addition, PD1 expression was higher in TLS + tumors than in TLS - tumors (IDDF2022-ABS-0161 Figure 1F). PCR results showed that TLS + HCC tissues had higher expression of LAG-3, Tim-3 and TIGIT (IDDF2022-ABS-0161 Figure 2A). These results revealed that immune cells infiltrating TLS + tumors are exhausted. Among 15 HCC patients receiving three cycles of anti-nivolumab treatment before surgical resection, 3 patients achieved complete pathological response (CPR) (IDDF2022-ABS-0161 Figure 2B). Patients achieving CPR had a certain degree of necrosis on contrast enhancement CT scan and the H&E staining figures (IDDF2022-ABS-0161 Figure 2C). Compared with non-responders, more CD8 + T cells infiltrated tumors of responders and tended to gather around TLSs (IDDF2022-ABS-0161 Figure 2D). Conclusions: Intra-tumoral TLSs predicted a poor prognosis in patients with HCC. Anti-PD1 treatment could educate TLS to develop antitumor activity and potentially reserve unfavorable clinical outcomes.